The structure of society - Abdul Razak, Nor Azam; Abdul Hakim, Roslan; Abd Karim, Mohd Zaini (The International Institute for Science, Technology and Education (IISTE), 2017)
This paper attempts to characterize the structure of society by examining the pattern of household expenditure, consumption, and saving of the lower, middle, and upper classes in Malaysia. The analysis is based on the household data taken from the Household Expenditure Survey of Malaysia in 2009/2010. The paper begins by arguing that the existing definitions of middle class fail to capture its essence as perceived by the society. Using a new definition, we find that the middle class constitutes about 60% of all households in the sample. By contrast, the lower class and upper class constitutes, respectively, 33.5% and 6.5% of all households in the sample. When the analysis is extended to cover the period 1998-2010, we find evidence of the shrinking lower class and the swelling middle class, signifying the presence of social mobility. We also find that the expenditure and consumption shares of income are pro-cyclical and the saving share of income is counter-cyclical for all income classes. When consumption is broken down into several sub-categories, we find that the idea of consumption smoothing appears to be most applicable to the upper class.